Experimental study of steel fiber prestressed concrete beam for shear, bending and torsion - Patil, Sudhir P.; Sangle, Keshav K. (Journal of Structural Engineering, 2024)
The low tensile strength and limited ductility, the unavoidable deficiency, of concrete can be overcome by the addition of fibres. In this research, an attempt was made to study the effects of flyash and steel fibers on shear, flexural and torsional strength of high strength prestressed concrete and steel fibre prestressed concrete beam specimens. To study the shear, flexural, pure torsion and combined bending-torsion strength behavior, the total 36 beam specimens of size 140mm x140mm x1500mm were castincluding 12 plain prestressed concrete beam specimens with 20% fly ash replacing to cement by its weight and 24 beam specimens by adding 20% fly ash replacing cement by its weight with1.5% steel fiber by weight of concrete. A primary finding emerging from the experimental program was that the placement of fibers, increased load carrying capacity of high strength fibre reinforced prestressed concrete beam. Steel fibres enhanced ductility, shear, flexural and torsional shear strength. All specimens were tested for single, double point loading, pure torsion, combined bending-torsion after 28 days. Deflections were measured. Experimental, analytical results were compared.